APPLYING TEAM QUIZ STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN ARABIC LANGUAGE (AN EXPERIMENTAL STUDY OF THE FIRST-YEAR FEMALE STUDENTS AT THE ISLAMIC STATE INSTITUTE OF LHOKSEUMAWE): تطبيق إستراتيجية فريق المسابقة لترقية نتائج تعلم اللغة العربية (دراسة تجريبية لطالبات الصف الأول بمعهد الجامعة الإسلامية الحكومية لهؤسماوي) - Salmawati, Salmawati (Institut Agama Islam Negeri Lhokseumawe, 2023)
This article is entitled Implementation of the Team Quiz Strategy to improve student learning outcomes in Arabic language lessons.